KIPRAH GENERASI MILENIAL PADA ERA 4.0 DALAM MEMBUMIKAN PANCASILA - Lestari, Aisyah Sri; Aini, Munifa; Fuadah Z, Anis (ATTA`DIB, 2019)
Pancasila is the basis of the Indonesian state, the birth of Pancasila through a long process by the founding fathers of the nation. Pancasila itself is a sacred state foundation because of the values contained in Pancasila. The millennial generation or the young generation is currently very instrumental in the development and enlightening of the nation. Millennial generation faces many challenges in the information age or 4.0 era. Not only domestic challenges but challenges from abroad must be faced by the Indonesian people, especially millennial generation. The hopes they have for the progress of the Indonesian people are implemented through actions that have a positive impact on the Indonesian people. Millennial generation gait in grounding the Pancasila starts from oneself and from the smallest things and invites the closest people to carry out the values contained in the Pancasila precepts.